2012
DOI: 10.1111/j.1742-1241.2012.02945.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of complementary and alternative medicine (CAM) use by the general population: a systematic review and update

Abstract: Summary Objectives:  To update previous systematic reviews of 12‐month prevalence of complementary and alternative medicine (CAM) use by general populations; to explore trends in CAM use by national populations; to develop and apply a brief tool for assessing methodological quality of published CAM‐use prevalence surveys. Design:  Nine databases were searched for published studies from 1998 onwards. Studies prior to 1998 were identified from two previous systematic reviews. A six‐item literature‐based tool was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
368
6
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(423 citation statements)
references
References 62 publications
11
368
6
18
Order By: Relevance
“…Our findings revealed a strong belief in the possible role of CAM for HIV management, consistent with an earlier Malaysian study by Hasan et al reported 30%-100% use of CAM among PLWHA. [19] This substantial prevalence of CAM use among HIV population has also been reported elsewhere [15,29,[31][32][33][34][35], including the developed countries. [16] Remarkably, most participants believed in CAM use to complement conventional ARTs but not to replace it, and were of the opinion that the best time to use CAM is when ARTs are yet to be initiated.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings revealed a strong belief in the possible role of CAM for HIV management, consistent with an earlier Malaysian study by Hasan et al reported 30%-100% use of CAM among PLWHA. [19] This substantial prevalence of CAM use among HIV population has also been reported elsewhere [15,29,[31][32][33][34][35], including the developed countries. [16] Remarkably, most participants believed in CAM use to complement conventional ARTs but not to replace it, and were of the opinion that the best time to use CAM is when ARTs are yet to be initiated.…”
Section: Discussionmentioning
confidence: 80%
“…[15] Hence, despite the proven efficacy of ARTs, approximately 60% of PLWHA use CAM. [14] A majority of these patients believe that CAM improves general wellbeing, boosts energy levels and enhances the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2002, the proportion of adults in the United States who has used complementary or alternative therapies has risen from 36 percent to 42 percent or higher [2,3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increasing numbers of people have sought complementary and integrative health (CIH) care in the United States [1] and worldwide [2]. The Centers for Disease Control reports that 38% of adults in United States have used one or more complementary and alternative medicine (CAM) practices in a 12-month period [3].…”
Section: Introductionmentioning
confidence: 99%